М. М. Аркас: аспекти культурної ідентифікації - Чеботаєва, О. (Краєзнавство, 2018)
Здійснюється спроба культурологічного аналізу особистості М. М. Аркаса. Уточнюється зміст категорії «просвітництво», що інтегрально виражає сутність соціокультурної місії М. М. Аркаса. Значна
увага приділяється ролі родинно-династичної традиції як чинника концентрації духовної і творчої енергії. Аналізуються історичні прояви греко-української культурної взаємодії як один з плідних векторів аккультурації на півдні України. The article contains an effort of culturological analysis of personality of M. M. Arkas. It globally determines
the system of culturally indentifying criteria of this outstanding social and cultural phenomenon of Mykolaiv Region
and Southern Ukraine. The content of the category «enlightenment» is specified. This category integrally expresses the
essence of social and cultural mission of M. M. Arkas. Much attention is also paid to the role of family-dynastic tradition
as a factor of spiritual and creative energy accumulation. M. M. Arkas is depicted as a representative of the
unique ancestral line, five generations of which for the past 125 years took the most active part precisely in those aspects
of Mykolaiv and Southern Ukraine's life, which determined the regional cultural distinguishing features.
The article analyzes the historical demonstrations of the Greek-Ukrainian cultural interaction as one of the
productive vectors of acculturation in the south of Ukraine. It is noted that this phenomenon formed both «the
Greeks with Ukrainian soul» and the Ukrainians with the Hellenistic worldview. An invaluable merit of the latter
was their compatriots’ inclusion to ancient heritage, which was and still remains the primary source of forms and
meanings of European culture. The author concludes that the personality, creative and public activity of
M. M. Arkas are reflecting a number of typical regional social and cultural tendencies. On the other hand,
M. M. Arkas represents a rare (both now and always) type of personal and family enlightenment selfless devotion.
From this angle, he is a moral benchmark not only for the local community, but for the nation as a whole. Осуществляется попытка культурологического анализа личности Н. Н. Аркаса. Уточняется содержание категории «просветительство», интегрально выражающей сущность социокультурной миссии
Н. Н. Аркаса. Значительное внимание уделяется роли семейно-династической традиции как фактора
концентрации духовной и творческой энергии. Анализируются исторические проявления греко-украинского культурного взаимодействия как одного из продуктивных векторов аккультурации на юге Украины.